MENINGKATKAN KECERDASAN EMOSIONAL MELALUI METODE BERCERITA PADA KELOMPOK A DI PAUD VIVEVI CERIA SERANG-BANTEN - Zahrah Choiriah (Early Childhood Teacher Education Department UNIVERSITAS SULTAN AGENG TIRTAYASA, 2016)
This study aims to (1) understand the process of implementing storytelling in improving emotional intelligence of children in group A PAUD VIVEVI Ceria Serang, Banten, and (2) To know the improving of emotional intelligence of children in group A PAUD VIVEVI Ceria Serang, Banten after using storytelling. This type of this research is Classroom Action Research by using Kemmis and Mc Taggart research model. Subjects were 12 children in group A PAUD VIVEVI Ceria Serang, Banten. The research object is emotional intelligence. Methods of data collection conducted through observation, interviews and documentation. Data analysis technique conducted in qualitatively and quantitatively. Indicators of success in this research was 65%. Based on the research results (1) stages of the storytelling process such as: storytelling preparation, implementation and evaluation storytelling. Besides storytelling method were interesting and fun activity, storytelling is also one methods to develop the thought power and imagination of children, be able to develop child development aspect, be able to build a character or characters, giving entertainment for children as a learning method used to provide information (2) improving emotional intelligence through storytelling can be seen as: a child is able to express their feelings, express emotions of anger, sadness, envy, the child is able to entertain themselves, children are able to control themselves from heart desires or refraining from satisfaction, the child is able to confidently, children have a sense of responsibility, the child is able to be sensitive for other people feelings and children easy to sosialized with others. The results showed that emotional intelligence of children increased to 71.59% from the pre-research of 39.37% increased first cycle amounted 54.24% from these results we can conclude that storytelling can improve emotional intelligence in children in group A PAUD VIVEVI Ceria Serang-Banten.